Peran Tanda Kecakapan PMR Dalam Pendidikan Berbasis Kemanusiaan - Hany Arifya; Diana Eka Pratiwi; Fadhilah Khoiriyah; Usiono U (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The Youth Red Cross (PMR) proficiency badge is an integral part of the Indonesian Red Cross (PMI) efforts to educate the younger generation in skills, character, and humanitarian values. This study aims to analyze the role of the PMR proficiency badge in humanitarian-based education through the Systematic Literature Review (SLR) approach. Data were obtained from articles, official PMI documents, and reports of activities related to PMR. The results of the study indicate that the proficiency badge contributes to building technical skills such as first aid and disaster preparedness, while instilling the values of solidarity, empathy, and leadership. However, challenges in implementation, such as the lack of uniform training standards, require more attention. Recommendations include improving instructor training, developing educational modules, and optimizing technology for monitoring.